The impact of Cookie Consent Notices on user’s privacy concerns : an empirical analysis - Bellentani, Tommaso Maria (2020)
Online privacy has become a significant issue in our society with the use of personal information widespread by websites and firms. To regulate this market, the European Union adopted the General Data Protection Regulation to protect online privacy and give back power to users, requiring firms to recover consent before gathering users’ personal information. Therefore, websites introduced cookie consent notices that allow users to specify their choice regarding the management of personal data. However, this design can manipulate user’s privacy concerns while navigating the website. To find out how, we developed an experiment divided into two steps: before, users displayed a cookie consent notice and, following, they answered to a set of ten questions with different intrusiveness levels, we aimed to measure the correlation between these two phases. We used the platform Amazon Mechanical Turk to gather data building a database of 320 respondents that we tested running random effects panel logistic models. We found out that users displaying a cookie consent notice with pre-ticked choices increase their privacy concerns when they face it without a “reject all” bulk option or when they answer to intrusive questions. Furthermore, we found out that users acting to protect their privacy tend to disclose more intrusive information and that users with a high level of privacy concern disclose less information compared to the others.